2018
DOI: 10.18632/oncotarget.23968
|View full text |Cite
|
Sign up to set email alerts
|

Differential tumor biological role of the tumor suppressor KAI1 and its splice variant in human breast cancer cells

Abstract: The tetraspanin and tumor suppressor KAI1 is downregulated or lost in many cancers which correlates with poor prognosis. KAI1 acts via physical/functional crosstalk with other membrane receptors. Also, a splice variant of KAI1 (KAI1-SP) has been identified indicative of poor prognosis. We here characterized differential effects of the two KAI1 variants on tumor biological events involving integrin (αvß3) and/or epidermal growth factor receptor (EGF-R). In MDA-MB-231 and -435 breast cancer cells, differential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…38,41 Interestingly, the expression of some tumor suppressor genes, such as LKB1 and KLF6, was controlled by splicing alterations. 2,6,42 In the present study, we showed that WEE1 expression is also altered through alternative splicing by DDX56 overexpression. RNA sequence analysis showed that knockdown of DDX56 immediately reduced the intron retention of WEE1 (truncated WEE1) and increased wild-type WEE1 mRNA expression.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…38,41 Interestingly, the expression of some tumor suppressor genes, such as LKB1 and KLF6, was controlled by splicing alterations. 2,6,42 In the present study, we showed that WEE1 expression is also altered through alternative splicing by DDX56 overexpression. RNA sequence analysis showed that knockdown of DDX56 immediately reduced the intron retention of WEE1 (truncated WEE1) and increased wild-type WEE1 mRNA expression.…”
Section: Discussionsupporting
confidence: 60%
“…The expression of WEE1 is suppressed in colon cancer and non‐small cell lung cancer . Interestingly, the expression of some tumor suppressor genes, such as LKB1 and KLF6 , was controlled by splicing alterations . In the present study, we showed that WEE1 expression is also altered through alternative splicing by DDX56 overexpression.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, CD82 was observed to inhibit cell adhesion which could possibly be mediated via its interaction with integrins [48]. The metastasis suppressive functions of CD82 have been reported to be abrogated by the splicing of the CD82 gene [50,51], where the CD82 spliced variant was observed to enhance cell migration and proliferation, concomitant with the activation of Src kinase in MDA-MB-231 breast cancer cells [50]. Overexpression of Sulfatase 2 (Sulf 2) was also reported to promote cell migration and invasion with the concomitant downregulation of CD82 expression in MDA-MB-231 breast cancer cells [52].…”
Section: Significance Of Cd82 Expression As a Metastasis Suppressor In Different Types Of Cancer 41 Breast Cancermentioning
confidence: 99%
“…Moreover, there is another isoform with a shortened LEL (CD82 Iso4), from which the mRNA is unknown, wherefore we cannot evaluate its expression probability. Still, from published data we can safely conclude that this isoform expresses at levels that affect cellular function 43 .…”
Section: Resultsmentioning
confidence: 93%